Study on Growth Performance of Native Chicken by Used diet from Local Ingredient - KEOMANY, Daosavanh; XAYKOSY, Salakham; SISAMOUTH, Souksavanh; VONGNADY, Konh (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This the experiment was conducted at experiment center of Animal Science Department, Agriculture and Environment Faculty, Savannakhet University (Nongphue campus), Kaisone Phomvihanh City, Savannkhet Province. The aims of this experiment were studies on growth performance of native chicken by used diet from local ingredient. The experiment was used 80 chickens (8 weeks of age) and were allocated into 4 groups with 4 replications: Treatment 1 (T1): Paddy rice meal 100% (control); Treatment 2 (T2): Paddy rice meal 30% + Broken rice 30%+ rice bran 18 %+ cassava root 12% + fish meal 10 %; Treatment 3 (T3): Paddy rice meal 30% + Broken rice 30% + rice bran 13 % + cassava root 12% + fish meal 15%; Treatment 4 (T4): Paddy rice meal 30% + Broken rice 30%+ rice bran 13 % + cassava root 12% + fish meal 20% by completely randomized design (CRD) model. The result of this experimental showed that: the weight of chicken week 0 – week 1 was not significant (P-value>0.05), but the weight of chicken form week 2- week 8 were significant (P-value<0.05). The comparison between treatment on final live weight, the best treatment were: T4, T2, T3 and T1 (564.9, 549.8, 548.3 and 449.4g/head, respectively); ADG on final week the highest were: T4, T2, T3, T1 (44.9, 42.3, 39.5 and 18.8g/ head /day) respectively and there were significant (P-value<0.05) (and FCR are the same trend of ADG:) T4, T2, T3 and T1 (1.10, 1.14, 1.15 and 1.21) respectively and there were significant (P-value<0.05).